Highly ion-selective sulfonated poly (4,4′-diphenylether-5,5′-bibenzimidazole) membranes for vanadium redox flow battery - Yufei Gao; Chunxue Wang; Han Ye; Ying Zhang (Journal of Experimental Nanoscience, 2024)
Renewable energy requires long-duration energy storage technologies, of which vanadium flow battery is regarded as the most suitable candidate for safe and long-duration energy storage applications. However, vanadium flow batteries still suffer from capacity decay and low power density, which arise from membrane degradation and high resistance. Herein, a sulfonated poly (4,4′-diphenylether-5,5′-bibenzimidazole) (SOPBI) membrane is reported for use in vanadium redox flow batteries. The prepared SOPBI membranes show an area resistance of 0.63 Ω cm2 at room temperature after doped with 3 M H2SO4. Moreover, membranes with 3 M H2SO4 doping exhibit tensile stress at break of 15.1 MPa. Benefiting from the SOPBI membrane, the all-vanadium redox flow battery delivers a superior energy efficiency of 77.7% at 140 mA cm−2 while operating stably at a current density of 120 mA cm−2 for 200 cycles.